Hyoid displacement patterns in healthy swallowing - Maria Regina Macedo Alves; Isabella Christina Oliveira Neto; Guilherme Maia Zica; Henrique Lederman; Maria Inês Rebelo Gonçalves (Einstein (São Paulo), 2022)
ABSTRACT Objective To describe the patterns of displacement of the hyoid bone in healthy individuals, considering their displacements during swallowing of different consistencies. Methods Two hundred one swallowing videofluoroscopy exams of 67 adult and elderly individuals without swallowing disorders were analyzed. Descriptive analysis was performed to identify and describe the patterns of displacement of the hyoid bone. Results Seven types of displacement of the hyoid bone were found: H1 (horizontal), H2 (short vertical and long horizontal), H3 (vertical and diagonal to upper), H4 (long vertical and short horizontal), H5 (vertical), H6 (diagonal), and H7 (brief). The standards were maintained in different consistencies. The most frequent pattern of displacement was type H2. The distribution of the types of displacement of the hyoid was different among men and women. Conclusion Seven patterns of displacement of the hyoid bone during swallowing of normal adults and older people have been described. The most frequent pattern of displacement was horizontal, with variations in distribution between men and women. The displacement pattern was maintained during the swallowing of the three different consistencies (thin, pasty and solid liquid).